Flow cytometric features of lymphoid subsets in healthy and diseased cats - Meneses-Nava, Cesar Guillermo; Ubiali, Alessandra; Dossi, Greta; Hammer, Sabine E.; Rütgen, Barbara C.; Locatelli, Chiara; Stranieri, Angelica; Martini, Valeria (Frontiers in Veterinary Science, 2025)
IntroductionFlow cytometry (FC) is widely used in humans and dogs to diagnose and characterize hematopoietic neoplasms. Conversely, its use in feline patients is still limited, leading to a lack of standardized protocols and subjective data interpretation.MethodsHerein, we describe FC features of circulating lymphoid subsets in a total of 20 cats: 9 healthy cats, 6 diseased cats without hematopoietic neoplasm, and 5 cats with probable chronic lymphocytic leukemia (CLL), using a panel of 10 antibodies and a multicolor approach, in terms of both cell size (nFSC) and degree of antigen expression (MFI).ResultsThree main subsets were identified in healthy cats and diseased cats without hematopoietic neoplasm (namely, CD5 + CD45R-, CD21 + CD45R + and CD5 + CD45R+). CD4 + CD8- cells outnumbered CD4- CD8 + cells. Low percentages of CD4 + CD8 + and CD134 + cells were also present. MHCII had higher fluorescence intensity in B- than in T-cells. CD9 was not expressed on leukocytes surface, but on small events possibly referable to platelet clumps. In diseased cats without hematopoietic neoplasm, each T-cell subset was larger in size than in healthy cats. Finally, in cats with probable CLL the leading phenotype was CD5 + CD45R-CD4 + CD8-CD134 + MHCII+ and cell size overlapped with the one of the other diseased cats.DiscussionOur results are expected to lay the ground for a more standardized approach to feline samples for FC, and a more objective data interpretation, ultimately leading to improved diagnostic accuracy. Further studies are needed to assess the biological, diagnostic and prognostic value of specific FC patterns in feline medicine.